2021
DOI: 10.30656/sm.v6i2.2963
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Work Family Conflict dan Stres Kerja Pada Kinerja Ibu Bekerja Dari Rumah Selama Pandemic Covid 19 di Bandung

Abstract: Penyebaran virus covid 19 membuat para pemberi kerja memberlakukan untuk bekerja dari rumah. Pada rentang waktu Work From Home terjadi penurunan produktivitas dari beberapa sektor, tingkat perceraian di kota Bandung meningkat 38%. hal ini menimbulkan beberapa problematika berkaitan dengan kinerja.Penelitian ini bertujuan untuk mengetahui gambaran serta besaran pengaruh work family conflict dan stres kerja terhadap kinerja pada ibu yang bekerja dari rumah saat pandemi covid 19 di Kota Bandung. Metode yang digun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Setiawati (2020) states that there is an effect of work stress on teacher performance. A similar study was also conducted by Retnowati et al, (2020) but found no effect of work stress on performance. Thus, the proposed hypothesis is as follows: H1: Work from home has a significant effect on performance H2: Work from home ha s a significant effect on job stress H3: Job stress has a significant effect on performance Work stress is influenced by several factors, both internal and external factors.…”
Section: Hypothesis Development Relationship Between Two or More Vari...mentioning
confidence: 54%
“…Setiawati (2020) states that there is an effect of work stress on teacher performance. A similar study was also conducted by Retnowati et al, (2020) but found no effect of work stress on performance. Thus, the proposed hypothesis is as follows: H1: Work from home has a significant effect on performance H2: Work from home ha s a significant effect on job stress H3: Job stress has a significant effect on performance Work stress is influenced by several factors, both internal and external factors.…”
Section: Hypothesis Development Relationship Between Two or More Vari...mentioning
confidence: 54%
“…X7 and Mrs. X8 also helps provide an explanation of how to regulate your emotions, among them by taking an individual approach, dividing the workload not only on one staff, and trying to make the work atmosphere more comfortable by listening to music, due to the workload you are experiencing (Afif, 2020, andJulianti, 2021). Retnowati et al, (2020). It is important to know that the roles of clinical and general psychologists in handling high workloads and deadlines complement each other.…”
Section: Resultsmentioning
confidence: 99%
“…Mrs. X7 and Mrs. X8 as a supporting informant also provides an explanation of the symptoms of burnout syndrome resulting from work deadlines and provides input regarding this matter. The role of clinical and general psychologists in reducing the workload and deadline pressure felt by staff in the context of their work is critical in supporting individual mental wellbeing and productivity (Jane, (2017), Norhayati, (2021), andRetnowati et al, (2020). It is important to know that the roles of clinical and general psychologists in handling high workloads and deadlines complement each other.…”
mentioning
confidence: 99%
“…In this situation, Work Family Conflict experienced by a mother while working at home included, Mother felt less productive at work because of inadequate support facilities, it was difficult to finish work quickly so that it affected the performance of a mother. (25) In the other research by (26) during a pandemic, if a company implements reduced working hours and work flexibility during Work From Home (WFH) it is felt that it helps mothers to adapt to working hours and carrying out their roles and responsibilities at home. This is what helps reduce work family conflict during WFH.…”
Section: "Working Mom" During Pandemicmentioning
confidence: 99%